PENGARUH ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN - ICHWAN, CHOIRUL (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Fast food beverage business competition in Indonesia is very strict. When visiting the malls will be easy to find a new trend is emerging. There are a number of specific beverage outlets offering drinks tea. The amount is also more and more with the brand that more and more. To win this competition the company is required to conduct a marketing strategy. One of them is building a product attribute. The strategy also used by fast food beverage company tear a cat to influence purchasing decisions at the royal plaza food court visitors Surabaya. The test results simultaneously using the F test indicates that the variable attributes of a product consisting of price, service, privilege and sense of having a significant influence on product purchase decision variables tears cat food court at the Royal Plaza Surabaya. a=0,05 significance level.Significance value of 0000 which is less than The test results are partially using T test showed that the variable price, service, privilege and a sense of having a significant influence on purchase decision variables. Retrieved price variable significance value 0033, 0002 Provided service variables, the variables obtained significance privilege 0006. 0001 acquired a sense of significance of variables then the value is less than the significance level of signfikansi0.05. Keyword: Product attributes, price, service, privilege, taste, Purchasing Decision